THE EFFECT OF GUIDED DISCOVERY LEARNING MODEL ON STUDENT’S ACHIEVEMENT AT CHARACTERISTICS OF WAVE TOPIC IN SMA N 1 MEDAN CLASS XI ACADEMIC YEAR 2014/2015 - Yohana Glorya Tobing; Alkhafi Maas Siregar (UNIVERSITAS NEGERI MEDAN, 2016)
ABSTRACT The aim of this research was to find the effect of guided discovery learning model on student’s achievement at characteristics of wave topic in SMA N 1 Medan class XI academic year 2014/2015. The research method was quasi-experiment. The populations were all 2nd grade students odd semester consist of 13 classes in SMA N 1 Medan. The samples of this research conduct two classes and consist of 37 students from experiment class and control class defined by cluster random sampling. The results that were obtained: post-test mean value of the experiment class was 75.94 and 75.02 for control class. Standard deviation for two classes was 14.94 and 12.48. Normality of the test result from the both samples was normal and homogeneous. So, there was the significant effect of using guided discovery learning model. It can conclude that studying with guided discovery learning model was higher than direct instructional learning model. Key word: guided discovery learning, student’s learning achievement, learning model, physics